Spirituality and Healthy Lifestyle Behaviors: Stress Counter-balancing Effects on the Well-being of Older Adults - Boswell, Gracie H. (Journal of religion and health, 2006)
The goal of this study was to examine stress-ameliorating effects of religiosity, spirituality, and healthy lifestyle behaviors on the stressful relationship of chronic illness and the subjective physical well-being of 221 older adults. We also investigated whether the intervening variables functioned as coping behaviors and orientations or as adaptations in late life. Guided by the stress paradigm, path analysis was used to assess these relationships in a stress suppressor model and a distress deterrent model. No suppressor effects were found; however a number of distress deterrent relationships were detected. Spirituality, physical activities, and healthy diet all contributed to higher subjective physical well-being, as counter-balancing effects, in the distress deterrent model. The findings have implications for future research on the role of spirituality, religiosity and lifestyle behaviors on the well-being of chronically ill older adults. Findings also support the need for studying different dimensions of religiosity and spirituality in an effort to understand coping versus adaptation in behaviors and orientations.